2018
DOI: 10.1111/ajpy.12201
|View full text |Cite
|
Sign up to set email alerts
|

Adult attention deficit/hyperactivity disorder among the prison inmates: An investigation of the executive function differences and comorbidity effects

Abstract: Objective: Attention deficit/hyperactivity disorder (ADHD) is one of the most prevalent psychiatric disorders that often persist into adulthood. ADHD is associated with a high percentage of comorbid psychiatric disorders. Studies indicate that ADHD is prevalent among inmates. The aim of the present study was to evaluate the executive functions (EFs), that is, inhibition and working memory among inmates with and without ADHD after controlling for comorbidity effects. Method: Through stratified sampling method, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
(78 reference statements)
0
0
1
1
Order By: Relevance
“…Contrary to previous ndings showing that individuals with ADHD exhibit di culties in cognitive control tasks that require inhibitory control (Hamzeloo et al, 2018;Sergeant et al, 2002;Thorell et al, 2017;Willcutt et al, 2005), our results did not reveal any difference in cognitive control ability (congruity effect) between individuals reporting ADHD symptoms and controls. Although numerous prior studies indicated cognitive control di culties among these individuals (for review see Craig et al, 2016), some failed to nd a difference between ADHD and typical individuals in cognitive control tasks (e.g., Spencer-Smith & Klingberg, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to previous ndings showing that individuals with ADHD exhibit di culties in cognitive control tasks that require inhibitory control (Hamzeloo et al, 2018;Sergeant et al, 2002;Thorell et al, 2017;Willcutt et al, 2005), our results did not reveal any difference in cognitive control ability (congruity effect) between individuals reporting ADHD symptoms and controls. Although numerous prior studies indicated cognitive control di culties among these individuals (for review see Craig et al, 2016), some failed to nd a difference between ADHD and typical individuals in cognitive control tasks (e.g., Spencer-Smith & Klingberg, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…33.4 ( n.a. ) 14 (56) IA 1 (4) HI 10 (40) C n.a n.a - + + Hadas et al ( 2021 ) Not enrolled 52 ADHD 49 HC 80.36 67.31 25.7 (0.5) 26 (0.3) n.a n.a n.a - (1 week) - n.a Hamzeloo et al ( 2018 ) Not enrolled 30 ADHD 30 HC 100 29.38 (6.10) n.a n.a 7.78, (2.48) n.a + + Kamradt et al ( 2014 ) Mixed 170 ADHD 83 HC 54.7 56.1 23.8 (4.7) 20.1 (2.9) 65 (38.2) IA 10 (5.8) HI 95 (55.8) C n.a n.a - (24 h to 48 h) + + Lampe et al ( 2007 ) Patient 22 (16) ADHD 20 (17) HC 63.63 30 29.95 (8.2) 28.7 (6.9) 14 (63.64) IA 1 (4.55) HI 7 (31.82) C 111.00 (11.6) 114.2 (8.5) n.a - (4 weeks) - - Linhartová et al ( 2021 ) Patient 26 ADHD 26 HC 73 ...…”
Section: Resultsunclassified